Pengaruh Solvabilitas, Profitabilitas, dan Opini Audit Terhadap Audit Delay pada Perusahaan Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2020-2023 - Jahan, Syarifah Nur; Nurdiwaty, Diah; Winarko, Sigit Puji (Business and Investment Review, 2024)
Audit delay in companies can lead to delays in reporting audited financial statements to the Financial Services Authority for publicly listed firms. Numerous factors contribute to audit delay. This study investigates the impact of solvency, profitability, and audit opinion as potential contributors to audit delay, both individually and collectively, among Consumer Goods Industry companies listed on the Indonesia Stock Exchange from 2020 to 2023. Using a quantitative approach and secondary data, the study analyzed 164 annual financial reports from 41 companies. Analytical methods included descriptive statistics, classical assumption tests, Multiple Linear Regression analysis, determination coefficients, and hypothesis testing using IBM SPSS Statistics 23 software. Findings indicate: (1) Solvency and audit opinion individually do not significantly influence audit delay. (2) Profitability has a significant partial effect on audit delay. (3) Simultaneously, solvency, profitability, and audit opinion collectively exert a significant influence on audit delay.